THE INFLUENCE OF A CERTAIN PATHOLOGY ON THE REGULATORY-ADOPTIVE STATUS BY PATIENTS WITH ANGINA PECTORIS OF THE THIRD FUNCTIONAL CLASS - E. A. Mihalchuk (Кубанский научный медицинский вестник, 2015)
By 89 patients with angina pectoris of the third functional class (FC), a regulatory-adoptive status by parameters of cardio-respiratory synchronism was determined. The sick were divided in four groups by the presence of a certain pathology. In the first group 29 patients were included with the tensional angina pectoris without a pathology. The second group (20 patients) consisted of patients,whose angina pectoris went together with hypertonic disease, in the third-the patient with the tensional angina pectoris and the second type diabetes (20 patients),in the fourth-the patients with the tensional angina pectoris combined with hypertonic disease and the second type diabetes (20 patients). By the patients in the first group the regulatory-adaptive status was the highest. With the following diseases (hypertonic diseases, diabetes and their combinations) the status was getting lower. So, the following pathology by the patient with the tensional angina pectoris lessens their regulatory-adaptive status.